STATISTICAL ANALYSIS OF THE MAGNETIC FIELD MEASUREMENTS - Kozak, L.; Lui, A.; Savin, S. (Одеські астрономічні публікації, 2013)
Investigation of statistical features of the magnetic field fluctuations in bound regions of Earth's magnetosphere, on different time scales, is carried out in this work. Measurements of Cluster-II with frequency 22.5 Hz for 2004-2008 years have been used for the analysis. During these investigations we have studied the changes of shape and parameters of probability density function for magnetic field fluctuations for periods of presence of the satellite in magnetosheath, solar plasma wind and in region of magnetopause. We have considered the evolution of change of maximum of probability density function and investigated structure functions of different orders as characteristics of turbulent processes for different time scales. Investigation of structure functions of high orders helped us to determine the character of turbulent processes and study diffusion in the considered regions. We have found, that the highest intermittence is observed in the postshock region; for the middle magnetosheath the results of experimental data correspond to log-Poisson turbulent cascade model, and for the description of processes in SW plasma one can use the Iroshnikov-Kraichnan's model.